Efforts to Improve the Ability to Recognize Letters Through Alphabet Mini Book Media in Pembina II Public Kindergarten in Surabaya - Laelatul Koniah; Muhammad Reza (Wahana, 2023)
This study aims to improve children's ability to recognize letters through the alphabet mini book media. This research is a classroom action research conducted in 3 cycles. The subjects in this study were students in class A3 of TK Negeri Pembina II Surabaya, totaling 20 children consisting of 11 boys and 9 girls. Methods of data collection using observation and documentation. Data analysis technique uses simple descriptive statistics. The results showed that the ability to recognize children's letters increased, namely on the indicator mentioning the name of the letter in cycle 1 by 50 Percent, cycle 2 by 70 Percent, and cycle 3 by 85 Percent, the indicator mentioned the initial letter of the picture in cycle 1 by 35 Percent, cycle 2 by 65 Percent, and cycle 3 by 85 Percent, as well as indicators of writing letters in cycle 1 by 30 Percent, cycle 2 by 50 Percent, and cycle 3 by 80 Percent. Based on these results it can be concluded that the alphabet mini book media can improve the ability to recognize letters in children aged 4-5 years.